2009
DOI: 10.1007/s11999-009-1004-6
|View full text |Cite
|
Sign up to set email alerts
|

Can rhBMP-2 Containing Collagen Sponges Enhance Bone Repair in Ovariectomized Rats?: A Preliminary Study

Abstract: With an aging population the frequency of postmenopausal fractures is increasing. Methods to enhance the repair of osteoporotic bone repair therefore become more important to reduce the society burden of care. We asked if absorbable collagen sponges containing recombinant human bone morphogenetic protein-2 (rhBMP-2) have the potential to enhance bone repair. We randomly assigned 40 rats into the ovariectomy and sham operation groups. A segmental defect was created in the right tibia 12 weeks after ovariectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
(42 reference statements)
3
30
0
2
Order By: Relevance
“…It has been shown that local application of BMP2 significantly promotes spinal fusion, accelerates facture healing and enhances the repair of bone defects192021. Studies have also demonstrated that local BMP2 delivery induced prominent increases of bone formation rate in osteoporotic animals2223.…”
mentioning
confidence: 99%
“…It has been shown that local application of BMP2 significantly promotes spinal fusion, accelerates facture healing and enhances the repair of bone defects192021. Studies have also demonstrated that local BMP2 delivery induced prominent increases of bone formation rate in osteoporotic animals2223.…”
mentioning
confidence: 99%
“…In addition, orthogonal radiographs of harvested femora were obtained at sacrifice. Radiographs were scored for callus formation, quality of union, and bone remodeling by 2 independent blinded observers according to a published scoring system 28 .…”
Section: Methodsmentioning
confidence: 99%
“…20 In comparison, a hyaluronic acid (HA)-based carrier is injectable 21 Some studies have shown that rhBMP-2 increases the fusion rate or bone healing in osteoporosis animal models. [22][23][24] In addition, in ovariectomy sheep models, rhBMP-7 was delivered by inserting a poly-lactic glycolic acid microsphere to improve the vertebral body strength. 25 However, such studies showed only that rhBMP-2 and rhBMP-7 triggered new bone formations in osteoporosis models.…”
Section: Introductionmentioning
confidence: 99%